Study of the Physical Condition of Al-Azhar Pencak Silat Athletes in Kepahiang Regency - Gustian Ade Micola; Suwirman (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Physical condition is a fundamental determinant of athletes’ ability to perform effectively during training and competition. However, the physical capacities of athletes at the Al-Azhar Pencak Silat Association in Kepahiang Regency have not been objectively assessed to inform athlete development and performance enhancement. This study aimed to evaluate the physical condition of athletes at the association. A quantitative descriptive approach with a survey design was employed, involving physical testing and measurement. Of the 98 athletes in the study population, 30 were selected through stratified sampling. Cardiovascular endurance, agility, arm muscle strength, and lower-limb explosive power were assessed using the beep test, shuttle run, push-up test, and vertical jump test, respectively. Data were analyzed using frequency distributions and descriptive statistics. The results revealed that the athletes’ overall physical condition was classified as moderate, with a mean score of 13.50, indicating that their physical capacities require further improvement. The study concludes that more structured and systematic conditioning is necessary to optimize athletic performance. These findings provide coaches with an empirical basis for evaluating athletes’ physical capacities and developing targeted, systematic, and sustainable conditioning programs.